Smart Pigeonhole Alert System with SMS Notification - Omomule, Taiwo Gabriel; Adekile, Sekinat Bolanle; Ajayi, Olusola Olajide; Orimoloye, Segun Michael (International Journal of Computing Sciences Research; Vol 4 No 1 (2020): Vol 4, No 1, 2020)
Purpose – Most organizations are outdated in managing information with the use of conventional pigeonholes as message boxes for each member to track staff incoming and outgoing mails. Several challenges are experienced due to loss of relevant mails, untimely delivery and acknowledgement of incoming mails as well as late feedback. This paper proposes a mobile pigeonhole alert system using a sensor device to send an alert to the intended pigeonhole users notifying them of the arrival of a message as well as the need for timely feedback. Method – Hardware and software implementations were carried out using JAVA programming language to program a sensor, hardcoded on a micro-controller. A well-structured questionnaire was designed and administered to 200 pigeonhole users (i.e., lecturers) in an academic institution to elicit information about their perception of the usability and performance of the system. The data collected were subjected to statistical analysis using Statistical Package for Social Sciences (SPSS) software for correlation and regression analyses between the usability and system performance. Results – Statistical results showed that the system performed as expected based on users’ satisfaction, realization of system objectives and the significant values obtained from statistical analysis. Comparative analysis of the system also showed an improvement over other existing works. Conclusion – Information system is an essential aspect of any organization which helps with the dissemination and retrieval of information among members. Hence, the designed system has facilitated the work of office clerks as well as the pigeonhole users by reducing the stress of daily pigeonhole check-in and allows quick feedback mechanism for smooth record and operation to urgent mails. Practical Implications – An efficient platform for information retrieval and notification has been developed. Users found it convenient to manage memos, letters and other relevant documents without delay and in a timely fashion.